Bacterial single cell protein from methanotrophic bacteria as an alternative ingredient for gilthead seabream (Sparus aurata) aquafeeds: Effects on digestibility, growth performance, gut microbiota, and disease resistance - Enric Gisbert; Alberto Ruiz; Federico Melenchón; Yanis Cruz-Quintana; Dolors Furones; Ignasi Sanahuja; Silvia Torrecillas; Nana W. Thorringer (Aquaculture, 2026)

Coronavirus in European hedgehogs (Erinaceus europaeus) from Denmark before and during the COVID-19 pandemic - Sophie Lund Rasmussen; Rosanna Zobba; David W. Macdonald; Emanuela Bazzoni; Laura Iacolina; Carla Cacciotto; Cino Pertoldi; Massimiliano Guerra; Alessandra Scagliarini; Alberto Alberti (Veterinary Microbiology, 2026)

PFA technology: Production, safety and wastewater deployment analysis - Jonathan I. Mendez-Ruiz; Kati Bell; John W. Norton; Charles Bott; Gaya Ram Mohan; Ralph Muvhiiwa; Shubhashini Oza; Kyriakos Manoli; Alberto Garibi; John Walton; Domenico Santoro (Water Research, 2026)

From Case Studies to Cohort of Patients: Automating FSI Simulations to Uncover Downstream Effects of Ascending Aortic Grafts - Ione Ianniruberto; Davide Astori; Simone Saitta; Davide Milesi; Pablo Villar Calle; Mario Gaudino; Leonard N. Girardi; Jay D. Humphrey; Jonathan W. Weinsaft; Emiliano Votta; Alberto Redaelli (Annals of Biomedical Engineering, 2026)
Purpose Open surgical repair with replacement of the diseased segment by a synthetic Dacron graft remains the standard treatment for ascending thoracic aortic aneurysms and dissections. However, post-operative sequelae, including dissection of the descending aorta (DA), have been reported and are often attributed to the mechanical compliance mismatch between the rigid graft and native aortic tissue. This mismatch can significantly alter downstream hemodynamics, potentially promoting adverse vascular remodeling and accelerating disease progression. Methods A fully automated patient-specific fluid–structure interaction (FSI) pipeline was developed to evaluate hemodynamic changes following graft implantation based on cardiac imaging: aortic 3D anatomy is reconstructed from Magnetic Resonance Angiography; aortic wall mechanics are described as anisotropic hyperelastic, with region-specific parameters calibrated from Cine-MRI-derived wall thickness and compliance data; blood flow is modeled using inlet velocity profiles derived from 4D flow MRI and Windkessel outlet conditions tuned to in vivo pressures. The computational workflow, implemented in the open-source software SimVascular, comprised three stages: (i) computational fluid dynamics simulation to determine blood pressures, (ii) structural analysis for prestress estimation, and (iii) FSI simulation coupling fluid and solid responses. It was applied to five patients whose images were collected pre-operatively, and post-operatively. Pre-operative and post-operative scenarios were then compared to assess whether the compliance mismatch due to the presence of the ascending graft alters the hemodynamic and biomechanics in the DA. Results The proposed framework successfully performed standardized, automated FSI simulations for all patients. Comparison between pre- and post-operative states revealed preliminary evidence of graft-associated flow remodeling, with consistent increases in flow-induced wall shear stress (WSS), oscillatory shear index, and Time Averaged WSS (TAWSS) in the aortic isthmus, which is commonly associated with post-operative dilation. Additionally, a topological analysis of WSS manifolds demonstrated a redistribution of fixed points from the ascending to the isthmus region after graft implantation, suggesting localized hemodynamic disturbances which may correlate with adverse biological responses. Conclusion This automated framework enables large-scale patient-specific FSI analyses and highlights preliminary biomechanical changes induced by aortic grafts. The high values of WSS observed in the isthmus region suggest that next-generation compliant grafts should be designed to mitigate downstream disease progression by lowering WSSs.

Combined change detection analysis of the impacts resulting from heavy rainfall events in mountainous areas - E. Matta; G. Nigrelli; W. Alberto; A. Filipello; M. Zittlau; M. Chiarle (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Associations between perfluoroalkyl substances and multiple sclerosis in U.S. cohorts compared with NMOSD, MOGAD, and healthy controls - Farren B.S. Briggs; Federico Montini; Charles F. Spurlock; Christine Ryan; Jessica N. Cooke Bailey; Erika S. Trapl; Guzel I. Shaginurova; Lukasz S. Wylezinski; Cheryl L. Sesler; Mahboobeh Fereidan Esfahani; Jessica Sagen; Hannah E. Gardener; et al. (Environmental Research, 2026)

Nutrient Enrichment Increases Grassland Biomass Sensitivity to Interannual Precipitation Variation - Ingrid J. Slette; Eric W. Seabloom; Carlos Alberto Arnillas; Jonathan D. Bakker; Dana Blumenthal; Jane A. Catford; Scott L. Collins; Nico Eisenhauer; Philip A. Fay; Magda Garbowski; Sylvia Haider; W. Stanley Harpole; et al. (Global Change Biology, 2026)
Primary production underpins much of ecosystem functioning and is often limited by nutrient and water availability. Ongoing global increases in nutrient inputs and interannual precipitation variability are thus likely to impact primary production, with unclear consequences for interannual variability in plant biomass. We used data from 35 grasslands in the Nutrient Network coordinated fertilization experiment to test if nutrient addition alters the response of plant biomass to year‐to‐year variation in growing season precipitation, and whether the effects of nutrient addition vary with factors such as site aridity or plant community composition. Nutrient addition increased biomass (by an average of 46% across sites), rain‐use efficiency (by 48%), and the sensitivity of biomass to interannual variation in precipitation (i.e., larger increase in biomass in wet years; by 13%), but did not change the strength of the interannual precipitation‐biomass correlation. Both sensitivity and correlation strength were higher in more arid sites, regardless of nutrient addition. These results suggest that grassland ecosystem functioning may become more variable from year to year as nutrient enrichment increases biomass sensitivity to precipitation and precipitation becomes more variable.

Soil Microbial Diversity and Network Organization Respond to Land Use and Agricultural Inputs Worldwide - Zaki Saati‐Santamaría; Sergio Pérez‐Gorjón; Daniel Abel‐Schaad; Alberto Acedo‐Bécares; Francisca Alba‐Sánchez; Amanda Lucia Alves; Weronika Babinska‐Wensierska; Jorge Ariel Marfetán; Carolina Barroetaveña; Kara Barry; Francisco Beitia; Katerina Biniari; et al. (Global Change Biology, 2026)
Soil microbiomes are critical for ecosystem functioning, yet the global influences of climate and agricultural practices on their diversity and structure remain incompletely characterized. Here we analyzed 1921 soil samples from 33 countries worldwide across diverse biomes to assess how climate gradients and agricultural inputs, including pesticides and fertilizers, shape prokaryotic and fungal communities. We found that microbial diversity peaks at intermediate temperatures and differs markedly between natural and agricultural soils, with agriculture increasing microbial diversity while altering community composition and ecological guilds. Pesticide use selectively reduced bacterial diversity and shifted fungal guilds, decreasing ectomycorrhizal fungi while increasing saprotrophs, whereas fertilization reduced microbial network cohesion, with organic and inorganic fertilizers eliciting distinct community responses. These findings reveal that climatic factors and agricultural management jointly influence soil microbial diversity, community structure, and network connectivity, with implications for soil health and ecosystem resilience in managed landscapes. Overall, our results demonstrate that agricultural practices, including the use of pesticides and both organic and inorganic fertilizers, act as strong ecological filters that reshape soil microbiomes worldwide—enhancing apparent diversity but driving a functional shift toward less mutualistic, more fragmented, and potentially less resilient communities.

Evaluation of four molecular detection assays for the diagnosis of Chlamydia pecorum infection in Victorian koalas (Phascolarctos cinereus) using Bayesian latent class analysis - Jack W. Wheelahan; Alberto Gomez-Buendia; Alistair R. Legione; Simon M. Firestone; Paola K. Vaz; Carol A. Hartley; Natalie L. Rourke; Joanne M. Devlin (Preventive Veterinary Medicine, 2026)

Distributed optical fibre sensing in physical oceanography: emergence and future prospects - Alberto C. Naveira Garabato; Carl P. Spingys; Andrew J. Lucas; Tiago S. Dotto; Christian T. Wild; Scott W. Tyler; Ted A. Scambos; Christopher B. Kratt; Giuseppe Cappelli; Ethan F. Williams; Mariona Claret; Hannah E. Glover; et al. (Ocean Science, 2026)
Distributed optical fibre sensing (DOFS) is a technology that enables continuous, real-time measurements of a range of environmental parameters along the length of a fibre optic cable. In this article, we review the recently emerged applications of DOFS techniques in physical oceanography and offer a perspective on the technology's potential for future growth within the field. The introduction of DOFS to physical oceanography is contextualised with a brief history of the technology, which spun off primarily from the use of seafloor-laid optical fibres for telecommunications purposes. The key components and underpinning physics of a DOFS system are outlined and, on their basis, the suite of variables that are observable with DOFS are discussed. The implementation factors of DOFS, which include trade-offs between measurement accuracy and spatio-temporal resolutions and ranges, are also examined. The physical oceanographic applications of DOFS to date are then illustrated with case examples of four distinct DOFS techniques: distributed temperature sensing (DTS), which can provide ocean temperature observations; distributed static strain sensing (DSS) and distributed acoustic sensing (DAS), which are sensitive to temperature, cable strain and strain-associated variables, such as pressure and ocean velocity; and ultra-long-range observations of ocean currents with optical interferometry. The forthcoming prospects of DOFS in physical oceanography are considered, and are proposed to include new fibre optic-based approaches to sense ocean salinity and measure through the water column. We conclude with reflections on the future role of DOFS within the Global Ocean Observing System, and highlight the opportunities provided by the existing world-wide network of seafloor-laid optical fibres.

Tamarixia citricola Hansson and Guerrieri sp. nov. (Hymenoptera: Eulophidae): a new parasitoid of Diaphorina citri Kuwayamava (Hemiptera: Psyllidae) found during a classical biological control program in Cyprus - Alberto Urbaneja; Meritxell Pérez-Hedo; Nicos Seraphides; Anthemis Melifronidou-Pantelidou; Stalo Giallouridou; Lia Markou; Menelaos C. Stavrinides; Chrysos Kaponas; Omar Ruíz-Rivero; David J. W. Morgan; Christer Hansson; Mark S. Hoddle; et al. (BioControl, 2026)
Asian citrus psyllid, Diaphorina citri , is a major global pest because it is the primary vector of Candidatus Liberibacter spp., the causal agents of huanglongbing (HLB), a lethal citrus disease. Following the detection of D. citri in Cyprus in 2023, the first record of this pest in the European Union, a classical biological control program targeting this pest was initiated in spring 2024 using the parasitoid Tamarixia radiata imported from California, USA. During field surveys in summer 2024, parasitized D. citri nymphs were found both in release and non-release orchards. T. radiata was recovered from release sites, confirming its establishment. In contrast, parasitism in non-release orchards suggested the presence of native or unintentionally introduced parasitoids, or a rapid spread of T. radiata into new areas. To determine the identity of parasitoids associated with D. citri in Cyprus, an integrative approach was adopted combining field observations, molecular analyses of the COI gene, and morphological analyses. T. radiata recovered from Cyprus field sites matched reference sequences of parasitoids from California. However, other specimens were genetically and morphologically distinct and represented a new species. The new species is described here as Tamarixia citricola Hansson and Guerrieri sp. nov. Taxonomic diagnoses and characters for separating both Tamarixia species associated with D. citri are provided. Results presented here indicate the coexistence of both T. radiata (introduced) and T. citricola (likely autochthonous) in Cyprus citrus orchards. This finding has important implications for future biological control strategies and quarantine measures for D. citri in the Mediterranean basin.

B cell receptor stimulation inhibits class switch recombination through elevated DNA repair - Robert W. Maul; Rhonda L. McFleder; Zheng Cao; Darrell D. Norton; Jana Ridani; Philip Barbulescu; Alberto Martin; Javier M. Di Noia; Patricia J. Gearhart (DNA Repair, 2026)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Alarming conservation status of Western European steppe birds and their habitats: An expert-based review of current threats, traits and knowledge gaps - Julia Gómez-Catasús; Ana Benítez-López; Mario Díaz; David González del Portillo; Cristian Pérez-Granados; Juan Carlos Alonso; Beatriz Arroyo; Inmaculada Abril-Colón; Adrián Barrero; Rafael Barrientos; Luis Bolonio; Gerard Bota; et al. (Biological Conservation, 2025)

Land Use Interacts With Climate to Influence Microbial Diversity‐To‐Biomass Ratios Across Europe via Soil Organic Carbon and Nitrogen - José A. Siles; Alfonso Vera; Maëva Labouyrie; Johan van den Hoogen; Thomas W. Crowther; Ferran Romero; Leho Tedersoo; Carlos García; Arwyn Jones; Panos Panagos; Marcel G. A. van der Heijden; Alberto Orgiazzi; et al. (Molecular Ecology, 2025)
Ecosystem functioning is potentially dependent on the relationships between soil microbial diversity and biomass. Yet, it remains unclear how land use and climate influence these relationships. Here, we (i) analysed relationships and ratios between richness and biomass of bacteria and fungi in ~500 soils across Europe, including three land‐use types (woodlands, grasslands and croplands) and climates (cold, temperate and arid) and (ii) identified the driving factors of changes in richness:biomass (R:B) ratios. Richness and biomass of soil bacteria and fungi followed a unimodal pattern, with a peak in mid‐levels of biomass. This pattern was more evident in bacteria and more clearly exerted by land use than by climate. Bacterial R:B ratios decreased with land use in the following order: croplands > woodlands > grasslands. Fungal R:B ratios decreased as follows: grasslands > croplands > woodlands. Climate was found to interact with land use. In this way, arid climate tended to increase bacterial R:B ratios in the different land uses; however, the agricultural practices associated with croplands seem to buffer this effect. In fungi, the interactive effect of land use and climate was less straightforward than for bacteria. According to our models, soil organic carbon (SOC) and total nitrogen (N) in bacteria and SOC in fungi were identified as the primary predictors of R:B ratios. Therefore, factors related to climate and land‐use change with impact on SOC and N contents are potential disruptors of soil microbial R:B ratios. This study clarifies the diversity:biomass relationships across different land uses and climates.

Exploring high-intensity cropping rotations for improved yield and economic returns - Lucas P. Canisares; Helio W. Joris; Salathiel A. Teixeira; Claudio Kapp Junior; Lucas F.N. Souza; Carlos R. Pinheiro Junior; Martha L. Carvalho; Alberto M. Peper; Jônatas Galvan; Maurício R. Cherubin (European Journal of Agronomy, 2025)

Biological control mitigates spread of vector-borne plant pathogens - Kris A.G. Wyckhuys; Yi Zou; David W. Crowder; Evie Adriani; Annabelle B. Albaytar; Marie Joy B. Beltran; Ibtissem Ben Fekih; Carolina Camargo-Gil; Filomena C. Sta. Cruz; Lizette Cicero; Yelitza C. Colmenarez; Claudia M. Cuellar-Palacios; et al. (Agriculture, Ecosystems & Environment, 2025)

A room with a blue view: The impact of Blue Economy activities on housing prices across Scottish regions - Marcello Graziano; Maurizio Fiaschetti; John W. Gross; Karen A. Alexander; Alberto Longo; Tim O'Higgins (Journal of Rural Studies, 2025)

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Insights into the Movements and Habitat Use of Blue Marlins (Makaira nigricans) in the Southwestern Atlantic Ocean - Osman Crespo-Neto; Bruno C. L. Macena; Bruno Mourato; Eduardo G. Pimenta; Eduardo W. Wanick; José C. Pacheco; Alberto F. Amorim (Fishes, 2025)
Understanding the ecology of large pelagic fishes is important for species conservation and maintaining ecosystem dynamics. The Atlantic blue marlin (Makaira nigricans) is usually targeted in recreational fisheries and occasionally captured as bycatch in pelagic longline fisheries, yet it is considered an overexploited stock in the Atlantic. In this study, pop-up archival satellite tags were deployed on twenty-one blue marlins in the Southwest Atlantic Ocean between February 2006 and August 2021. Results show that blue marlin spent an average of 57% of their time in shallow waters (

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Magma storage and transport beneath the near-rift Fjallgarðar Volcanic Ridge, Northeast Iceland - Noëmi Löw; Sæmundur A. Halldórsson; Christoph Beier; Enikő Bali; Simon Matthews; Guðmundur H. Guðfinnsson; Edward W. Marshall; Jóhann Helgason; Eemu Ranta; Adam Abersteiner; Jaime D. Barnes; Alberto Caracciolo (Contributions to Mineralogy and Petrology, 2025)

First record of terrestrial vertebrates from a Late Pliocene-Early Pleistocene deposit in Cuba - Johanset Orihuela; Lázaro W. Viñola-Lopez; Logel Lorenzo; Alberto Clark; Yasmani Ceballos-Izquierdo (Journal of South American Earth Sciences, 2024)

Multiple genomic solutions for local adaptation in two closely related species (sheep and goats) facing the same climatic constraints - Badr Benjelloun; Kevin Leempoel; Frédéric Boyer; Sylvie Stucki; Ian Streeter; Pablo Orozco‐terWengel; Florian J. Alberto; Bertrand Servin; Filippo Biscarini; Adriana Alberti; Stefan Engelen; Alessandra Stella; et al. (Molecular Ecology, 2024)
The question of how local adaptation takes place remains a fundamental question in evolutionary biology. The variation of allele frequencies in genes under selection over environmental gradients remains mainly theoretical and its empirical assessment would help understanding how adaptation happens over environmental clines. To bring new insights to this issue we set up a broad framework which aimed to compare the adaptive trajectories over environmental clines in two domesticated mammal species co‐distributed in diversified landscapes. We sequenced the genomes of 160 sheep and 161 goats extensively managed along environmental gradients, including temperature, rainfall, seasonality and altitude, to identify genes and biological processes shaping local adaptation. Allele frequencies at putatively adaptive loci were rarely found to vary gradually along environmental gradients, but rather displayed a discontinuous shift at the extremities of environmental clines. Of the 430 candidate adaptive genes identified, only 6 were orthologous between sheep and goats and those responded differently to environmental pressures, suggesting different putative mechanisms involved in local adaptation in these two closely related species. Interestingly, the genomes of the 2 species were impacted differently by the environment, genes related to signatures of selection were most related to altitude, slope and rainfall seasonality for sheep, and summer temperature and spring rainfall for goats. The diversity of candidate adaptive pathways may result from a high number of biological functions involved in the adaptations to multiple eco‐climatic gradients, and a differential role of climatic drivers on the two species, despite their co‐distribution along the same environmental gradients. This study describes empirical examples of clinal variation in putatively adaptive alleles with different patterns in allele frequency distributions over continuous environmental gradients, thus showing the diversity of genetic responses in adaptive landscapes and opening new horizons for understanding genomics of adaptation in mammalian species and beyond.

Temporal Variation and Chemical Composition of Wet Atmospheric Deposition From Two Coastal Sites in the Gulf of Mexico - Javier Reyes-Trujeque; Alberto A. Espinosa; Rodolfo Sosa-Echeverría; Ana Luisa Alarcón-Jiménez; Pablo Sánchez-Álvarez; Jonathan D. W. Kahl (Water, Air, & Soil Pollution, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Timing of Cordilleran-Laurentide ice-sheet separation: Implications for sea-level rise - Alberto V. Reyes; Anders E. Carlson; Jorie Clark; Louise Guillaume; Glenn A. Milne; Lev Tarasov; Elizabeth C.B. Carlson; Feng He; Marc W. Caffee; Klaus M. Wilcken; Dylan H. Rood (Quaternary Science Reviews, 2024)

Intrinsic electrical conductivity of monolithic biochar - Randeep Gabhi; Kassie Tan; Tianjie Feng; Donald W. Kirk; Mauro Giorcelli; Alberto Tagliaferro; Charles Q. Jia (Biomass and Bioenergy, 2024)

Observing Antarctic Bottom Water in the Southern Ocean - Alessandro Silvano; Sarah Purkey; Arnold L. Gordon; Pasquale Castagno; Andrew L. Stewart; Stephen R. Rintoul; Annie Foppert; Kathryn L. Gunn; Laura Herraiz-Borreguero; Shigeru Aoki; Yoshihiro Nakayama; Alberto C. Naveira Garabato; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.

Deletion of TRPC6, an Autism Risk Gene, Induces Hyperexcitability in Cortical Neurons Derived from Human Pluripotent Stem Cells - Kyung Chul Shin; Gowher Ali; Houda Yasmine Ali Moussa; Vijay Gupta; Alberto de la Fuente; Hyung-Goo Kim; Lawrence W. Stanton; Yongsoo Park (Molecular Neurobiology, 2023)
Autism spectrum disorder (ASD) is a complex and heterogeneous neurodevelopmental disorder linked to numerous rare, inherited, and arising de novo genetic variants. ASD often co-occurs with attention-deficit hyperactivity disorder and epilepsy, which are associated with hyperexcitability of neurons. However, the physiological and molecular mechanisms underlying hyperexcitability in ASD remain poorly understood. Transient receptor potential canonical-6 (TRPC6) is a Ca 2+ -permeable cation channel that regulates store-operated calcium entry (SOCE) and is a candidate risk gene for ASD. Using human pluripotent stem cell (hPSC)–derived cortical neurons, single-cell calcium imaging, and electrophysiological recording, we show that TRPC6 knockout (KO) reduces SOCE signaling and leads to hyperexcitability of neurons by increasing action potential frequency and network burst frequency. Our data provide evidence that reduction of SOCE by TRPC6 KO results in neuronal hyperexcitability, which we hypothesize is an important contributor to the cellular pathophysiology underlying hyperactivity in some ASD.

Single cell protein from methanotrophic bacteria as an alternative healthy and functional protein source in aquafeeds, a holistic approach in rainbow trout (Oncorhynchus mykiss) juveniles - Alberto Ruiz; Ignasi Sanahuja; Nana W. Thorringer; Julie Lynegaard; Eleni Ntokou; Dolors Furones; Enric Gisbert (Aquaculture, 2023)

A common variant close to the “tripwire” linker region of NLRP1 contributes to severe COVID-19 - Vinicius N. C. Leal; Leandro M. Paulino; Raylane A. G. Cambui; Thiago G. Zupelli; Suemy M. Yamada; Leonardo A. T. Oliveira; Valéria de F. Dutra; Carolina B. Bub; Araci M. Sakashita; Ana Paula H. Yokoyama; José M. Kutner; Camila A. Vieira; et al. (Inflammation Research, 2023)

Butyrate decreases Campylobacter jejuni motility and biofilm partially through influence on LysR expression - Nereus W. Gunther; Alberto Nunez; Lori Bagi; Aisha Abdul-Wakeel; Amy Ream; Yanhong Liu; Gaylen Uhlich (Food Microbiology, 2023)

Ecosystem type drives soil eukaryotic diversity and composition in Europe - Julia Köninger; Cristiano Ballabio; Panos Panagos; Arwyn Jones; Marc W. Schmid; Alberto Orgiazzi; Maria J. I. Briones (Global Change Biology, 2023)
Soil eukaryotes play a crucial role in maintaining ecosystem functions and services, yet the factors driving their diversity and distribution remain poorly understood. While many studies focus on some eukaryotic groups (mostly fungi), they are limited in their spatial scale. Here, we analyzed an unprecedented amount of observational data of soil eukaryomes at continental scale (787 sites across Europe) to gain further insights into the impact of a wide range of environmental conditions (climatic and edaphic) on their community composition and structure. We found that the diversity of fungi, protists, rotifers, tardigrades, nematodes, arthropods, and annelids was predominantly shaped by ecosystem type (annual and permanent croplands, managed and unmanaged grasslands, coniferous and broadleaved woodlands), and higher diversity of fungi, protists, nematodes, arthropods, and annelids was observed in croplands than in less intensively managed systems, such as coniferous and broadleaved woodlands. Also in croplands, we found more specialized eukaryotes, while the composition between croplands was more homogeneous compared to the composition of other ecosystems. The observed high proportion of overlapping taxa between ecosystems also indicates that DNA has accumulated from previous land uses, hence mimicking the land transformations occurring in Europe in the last decades. This strong ecosystem‐type influence was linked to soil properties, and particularly, soil pH was driving the richness of fungi, rotifers, and annelids, while plant‐available phosphorus drove the richness of protists, tardigrades, and nematodes. Furthermore, the soil organic carbon to total nitrogen ratio crucially explained the richness of fungi, protists, nematodes, and arthropods, possibly linked to decades of agricultural inputs. Our results highlighted the importance of long‐term environmental variables rather than variables measured at the time of the sampling in shaping soil eukaryotic communities, which reinforces the need to include those variables in addition to ecosystem type in future monitoring programs and conservation efforts.

Chemical evaluation of pyrolysis oils from domestic and industrial effluent treatment station sludges with perspective to produce value-added products - Jonatas L. Rodrigues; Jacqueline de M. Campêlo; Alberto Wisniewski; Leandro W. Hantao; Marcos N. Eberlin; Jandyson M. Santos (Waste Management, 2023)

A human modified Pseudokossmaticeras brandti (Ammonitina: Kossmaticeratidae) from the late Campanian of Cuba and the species distribution in the Caribbean province - Esteban López-Murillo; Carlos Rafael Borges-Sellén; Alberto F. Arano-Ruiz; Lázaro W. Viñola-López; Yasmani Ceballos-Izquierdo; Johanset Orihuela; Neil H. Landman (Journal of South American Earth Sciences, 2023)

Ecological design of constructed wetlands in cold mountainous region: from literature to experience - Rachele Stentella; Alessio Cislaghi; Lorenzo M. W. Rossi; Luca Giupponi; Enzo Bona; Alberto Zambonardi; Luigi Rizzo; Francesco Esposto; Gian Battista Bischetti (Landscape and Ecological Engineering, 2023)

Reduction in size of the calcifying phytoplankton Calcidiscus leptoporus to environmental changes between the Holocene and modern Subantarctic Southern Ocean - Andrés S. Rigual-Hernández; Gerald Langer; Francisco Javier Sierro; Helen Bostock; José Manuel Sánchez-Santos; Scott Davidson Nodder; Tom W. Trull; Anne Marie Ballegeer; Andrew D. Moy; Ruth Eriksen; Laura Makowka; Thibauld M. Béjard; et al. (Frontiers in Marine Science, 2023)
The Subantarctic Zone of the Southern Ocean plays a disproportionally large role on the Earth system. Model projections predict rapid environmental change in the coming decades, including ocean acidification, warming, and changes in nutrient supply which pose a serious risk for marine ecosystems. Yet despite the importance of the Subantarctic Zone, annual and inter-annual time series are extremely rare, leading to important uncertainties about the current state of its ecosystems and hindering predictions of future response to climate change. Moreover, as the longest observational time series available are only a few decades long, it remains unknown whether marine pelagic ecosystems have already responded to ongoing environmental change during the industrial era. Here, we take advantage of multiple sampling efforts – monitoring of surface layer water properties together with sediment trap, seafloor sediment and sediment core sampling – to reconstruct the modern and pre-industrial state of the keystone calcifying phytoplankton Calcidiscus leptoporus , central to the global marine carbonate cycle. Morphometric measurements reveal that modern C. leptoporus coccoliths are 15% lighter and 25% smaller than those preserved in the underlying Holocene-aged sediments. The cumulative effect of multiple environmental factors appears responsible for the coccolith size variations since the Last Deglaciation, with warming and ocean acidification most likely playing a predominant role during the industrial era. Notably, extrapolation of our results suggests a future reduction in cell and coccolith size which will have a negative impact on the efficiency of the biological pump in the Southern Ocean through a reduction of carbonate ballasting. Lastly, our results tentatively suggest that C. leptoporus coccolith size could be used as a palaeo-proxy for growth rate. Future culture experiments will be needed to test this hypothesis.

Thermally-induced clumped isotope resetting in belemnite and optical calcites: Towards material-specific kinetics - Nathan Looser; Paul Petschnig; Jordon D. Hemingway; Alvaro Fernandez; Luiz Morales Grafulha; Alberto Perez-Huerta; Madeleine L. Vickers; Gregory D. Price; Max W. Schmidt; Stefano M. Bernasconi (Geochimica et Cosmochimica Acta, 2023)

Turtle barnacles have been turtle riders for more than 30 million years - Alberto Collareta; Michael W. Rasser; Eberhard Frey; Mathias Harzhauser (PalZ, 2023)
In contrast to other kinds of biological interactions, symbiosis is a scarcely investigated aspect of the fossil record. This is largely due to taphonomic biases that often frustrate any attempt to make a strong case that two organisms shared an intimate association in life. Among extant marine vertebrates, the sea turtles (Cheloniidae and Dermochelyidae) bear a broad and diverse spectrum of epibiotic symbionts, including specialists such as the turtle barnacles (Chelonibiidae and Platyleapadidae). Here, we reappraise an early Oligocene (Rupelian) fossil cheloniid skeleton, featuring the remains of cirripedes on the exterior of its entoplastron, from the Rauenberg fossil-lagerstätte , southwestern Germany. The barnacle specimens are assigned to Protochelonibia melleni , an extinct protochelonibiine species and the geologically oldest known member of Chelonibiidae. In the light of taphonomic and palaeoenvironmental considerations, and given that the extant chelonibiids are mostly known as epizoic symbionts of sea turtles, we conclude that this unique fossil association resulted from the epizoic growth of the barnacles on the external surface of the plastron of the turtle during its lifetime. This remarkable fossil association provides evidence that chelonibiids, including the extinct protochelonibiines, have been chelonophilic epizoans for more than 30 Myr. A survey of the trace and body fossil records shows that platylepadids are also likely as old as the Rupelian as is their symbiotic association with cheloniid hosts. This early emergence of the modern-looking, turtle-dwelling barnacle lineages corresponds to a climate-driven phase of major radiation and taxonomic turnover among sea turtles at the Eocene–Oligocene transition.

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

An experimental oil spill at a tidal freshwater wetland along the St. Lawrence River re-visited after 21 years - Lars Schreiber; Nathalie Fortin; Alberto Mazza; Christine Maynard; Jessica Wasserscheid; Julien Tremblay; Kenneth Lee; Charles W. Greer (Environmental Research, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

G﻿lobal phylogeography of ridley sea turtles (Lepidochelys spp.): evolution, demography, connectivity, and conservation - Sibelle Torres Vilaça; Anelise Torres Hahn; Eugenia Naro-Maciel; F. Alberto Abreu-Grobois; Brian W. Bowen; Jaqueline C. Castilhos; Claudio Ciofi; Nancy N. FitzSimmons; Michael P. Jensen; Angela Formia; Colin J. Limpus; Chiara Natali; et al. (Conservation Genetics, 2022)
Globally distributed marine taxa are well suited for investigations of biogeographic impacts on genetic diversity, connectivity, and population demography. The sea turtle genus Lepidochelys includes the wide-ranging and abundant olive ridley ( L. olivacea ), and the geographically restricted and ‘Critically Endangered’ Kemp’s ridley ( L. kempii ). To investigate their historical biogeography, we analyzed a large dataset of mitochondrial DNA (mtDNA) sequences from olive (n = 943) and Kemp’s (n = 287) ridleys, and genotyped 15 nuclear microsatellite loci in a global sample of olive ridleys (n = 285). We found that the ridley species split ~ 7.5 million years ago, before the Panama Isthmus closure. The most ancient mitochondrial olive ridley lineage, located in the Indian Ocean, was dated to ~ 2.2 Mya. Both mitochondrial and nuclear markers revealed significant structure for olive ridleys between Atlantic (ATL), East Pacific (EP), and Indo-West Pacific (IWP) areas. However, the divergence of mtDNA clades was very recent (< 1 Mya) with low within- clade diversity, supporting a recurrent extinction-recolonization model for these ocean regions. All data showed that ATL and IWP groups were more closely related than those in the EP, with mtDNA data supporting recent recolonization of the ATL from the IWP. Individual olive ridley dispersal between the ATL, EP, and IN/IWP could be interpreted as more male- than female-biased, and genetic diversity was lowest in the Atlantic Ocean. All populations showed signs of recent expansion, and estimated time frames were concordant with their recent colonization history. Investigating species abundance and distribution changes over time is central to evolutionary biology, and this study provides a historical biogeographic context for marine vertebrate conservation and management.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Rhodolith beds and their onshore transport in Fuerteventura Island (Canary Archipelago, Spain) - Ana Cristina Rebelo; Esther Martín-González; Carlos S. Melo; Markes E. Johnson; Alberto González-Rodríguez; Inés Galindo; Rui Quartau; Lara Baptista; Sérgio P. Ávila; Michael W. Rasser (Frontiers in Marine Science, 2022)
Rhodoliths occur extensively around the shores of Fuerteventura Island in the Canary Archipelago, with Lithothamnion cf. corallioides being the most prominent species. A large number of rhodoliths end up washed onshore, the debris from which contributes to the formation of sediments constituting modern beaches. In a previous study by one of the co-authors (MEJ), the northern coast of Fuerteventura was shown to comprise various types of rhodolith deposits such as beach, platform overwash, tidal pools, coastal dunes, and others. An extraordinary example of stranded rhodoliths is located near Caleta del Bajo de Mejillones, approximately 3 km west of Corralejo, on the north coast of the island. The deposit forms a supratidal beach 120 m long and 10 m wide that sits above the landward termination of an extensive wave-cut platform eroded in basalt and exposed at low tide to a width of 130 m perpendicular to shore. Here, rhodoliths are very small (<3 cm) resembling popcorn, and the locality is known as the “Popcorn Beach”. Other examples are berms up to 150 m long and 9 m wide at Caleta del Bajo de Mejillones, or an exposed beach at Playa del Hierro with an area of more than 1500 m 2 covered entirely of very coarse rhodolith sand. Extensive living rhodolith beds were found at a water depth of 22 m.

Human health risk–benefit assessment of fish and other seafood: a scoping review - Sofie Theresa Thomsen; Ricardo Assunção; Cláudia Afonso; Géraldine Boué; Carlos Cardoso; Francesco Cubadda; Alberto Garre; Johannes W. Kruisselbrink; Alberto Mantovani; János G. Pitter; Morten Poulsen; Hans Verhagen; et al. (Critical Reviews in Food Science and Nutrition, 2022)

New and overlooked occurrences of the rarely reported protochelonibiine “turtle” barnacles from the Oligocene and Miocene of Europe - Alberto Collareta; Mathias Harzhauser; Michael W. Rasser (PalZ, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Priming effects in soils across Europe - José A. Siles; Marta Díaz‐López; Alfonso Vera; Nico Eisenhauer; Carlos A. Guerra; Linnea C. Smith; François Buscot; Thomas Reitz; Claudia Breitkreuz; Johan van den Hoogen; Thomas W. Crowther; Alberto Orgiazzi; et al. (Global Change Biology, 2022)
Land use is a key factor driving changes in soil carbon (C) cycle and contents worldwide. The priming effect (PE)—CO 2 emissions from changed soil organic matter decomposition in response to fresh C inputs—is one of the most unpredictable phenomena associated with C cycling and related nutrient mobilization. Yet, we know very little about the influence of land use on soil PE across contrasting environments. Here, we conducted a continental‐scale study to (i) determine the PE induced by 13 C‐glucose additions to 126 cropland and seminatural (forests and grasslands) soils from 22 European countries; (ii) compare PE magnitude in soils under various crop types (i.e., cereals, nonpermanent industrial crops, and orchards); and (iii) model the environmental factors influencing PE. On average, PEs were negative in seminatural (with values ranging between −60 and 26 µg C g −1 soil after 35 days of incubation; median = −11) and cropland (from −55 to 27 µC g −1 soil; median = −4.3) soils, meaning that microbial communities preferentially switched from soil organic C decomposition to glucose mineralization. PE was significantly less negative in croplands compared with seminatural ecosystems and not influenced by the crop type. PE was driven by soil basal respiration (reflecting microbial activity), microbial biomass C, and soil organic C, which were all higher in seminatural ecosystems compared with croplands. This cross European experimental and modeling study elucidated that PE intensity is dependent on land use and allowed to clarify the factors regulating this important C cycling process.

Detection of the papaya strain of papaya ringspot virus (PRSV-P) in Paraguay - Arnaldo Esquivel-Fariña; Heron Delgado Kraide; Viviana Camelo-García; Jorge Alberto Marques Rezende; Elliot W. Kitajima (Journal of Plant Pathology, 2022)

Apolipoprotein E ɛ4–related effects on cognition are limited to the Alzheimer’s disease spectrum - Alberto Fernández; Lucía Vaquero; Ricardo Bajo; Pilar Zuluaga; Michael W. Weiner; Andrew J. Saykin; John Q. Trojanowski; Leslie Shaw; Arthur W. Toga; Laurel Beckett; Clifford R. Jack; Paul Aisen; et al. (GeroScience, 2022)
Whether the deleterious effects of APOE4 are restricted to the Alzheimer’s disease (AD) spectrum or cause cognitive impairment irrespectively of the development of AD is still a matter of debate, and the focus of this study. Our analyses included APOE4 genotype, neuropsychological variables, amyloid-βeta (Aβ) and Tau markers, FDG-PET values, and hippocampal volumetry data derived from the healthy controls sample of the ADNI database. We formed 4 groups of equal size ( n = 30) based on APOE4 carriage and amyloid-PET status. Baseline and follow-up (i.e., 48 months post-baseline) results indicated that Aβ-positivity was the most important factor to explain poorer cognitive performance, while APOE4 only exerted a significant effect in Aβ-positive subjects. Additionally, multiple regression analyses evidenced that, within the Aβ-positive sample, hippocampal volumetry explained most of the variability in cognitive performance for APOE4 carriers. These findings represent a strong support for the so-called preclinical/prodromal hypothesis , which states that the reported differences in cognitive performance between healthy carriers and non-carriers are mainly due to the APOE4’s capability to increase the risk of AD. Moreover, our results reinforce the notion that a synergistic interaction of Aβ and APOE4 elicits a neurodegenerative process in the hippocampus that might be the main cause of impaired cognitive performance.

Fine root dynamics across pantropical rainforest ecosystems - Walter Huaraca Huasco; Terhi Riutta; Cécile A. J. Girardin; Fernando Hancco Pacha; Beisit L. Puma Vilca; Sam Moore; Sami W. Rifai; Jhon del Aguila‐Pasquel; Alejandro Araujo Murakami; Renata Freitag; Alexandra C. Morel; Sheleme Demissie; et al. (Global Change Biology, 2021)
Fine roots constitute a significant component of the net primary productivity (NPP) of forest ecosystems but are much less studied than aboveground NPP. Comparisons across sites and regions are also hampered by inconsistent methodologies, especially in tropical areas. Here, we present a novel dataset of fine root biomass, productivity, residence time, and allocation in tropical old‐growth rainforest sites worldwide, measured using consistent methods, and examine how these variables are related to consistently determined soil and climatic characteristics. Our pantropical dataset spans intensive monitoring plots in lowland (wet, semi‐deciduous, and deciduous) and montane tropical forests in South America, Africa, and Southeast Asia ( n = 47). Large spatial variation in fine root dynamics was observed across montane and lowland forest types. In lowland forests, we found a strong positive linear relationship between fine root productivity and sand content, this relationship was even stronger when we considered the fractional allocation of total NPP to fine roots, demonstrating that understanding allocation adds explanatory power to understanding fine root productivity and total NPP. Fine root residence time was a function of multiple factors: soil sand content, soil pH, and maximum water deficit, with longest residence times in acidic, sandy, and water‐stressed soils. In tropical montane forests, on the other hand, a different set of relationships prevailed, highlighting the very different nature of montane and lowland forest biomes. Root productivity was a strong positive linear function of mean annual temperature, root residence time was a strong positive function of soil nitrogen content in montane forests, and lastly decreasing soil P content increased allocation of productivity to fine roots. In contrast to the lowlands, environmental conditions were a better predictor for fine root productivity than for fractional allocation of total NPP to fine roots, suggesting that root productivity is a particularly strong driver of NPP allocation in tropical mountain regions.

Vegetation fire activity and the Potential Fire Index ( PFIv2 ) performance in the last two decades (2001–2016) - Alex S. da Silva; Flavio Justino; Alberto W. Setzer; Alvaro Avila‐Diaz (International Journal of Climatology, 2021)
Fire incidence has been linked to multiple factors such as climate conditions, population density, agriculture, and lightning. Recently, fire frequency and severity have induced health problems and contributed to increase atmospheric greenhouse gases. Based on atmospheric susceptibility to fire, this study evaluates the use of a Potential Fire Index (PFIv2) to identify regions prone to fire development, as demonstrated by the satellite detected‐fire in the 2001–2016 interval. It is demonstrated that PFIv2 delivers an efficiency by up to 80% in matching the observed fires from Terra/MODIS satellite. The PFIv2 is also able to reproduce more accurately areas with fire activity with respect to its previous version, the PFI. This better performance is linked to the implementation of parameterization of water pressure deficit and atmospheric stability in the lower troposphere, and a new term to represent the effect of surface temperatures, particularly in mid‐latitudes and extra‐Tropics. To evaluate the performance of the PFIv2 in more details, its comparison to MODIS burned areas demonstrated correlations values higher than 0.6 over the most susceptible regions such as Africa and South America, slightly lower correlation is found where fire does not primary follows the climate annual cycle, and is dominated by high frequency events. These findings indicate that the PFIv2 can be an important tool for decision makers in predicting the potential for vegetation fires development and fire danger.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Assessing VIIRS capabilities to improve burned area mapping over the Brazilian Cerrado - Filippe L.M. Santos; Renata Libonati; Leonardo F. Peres; Allan A. Pereira; Luiza C. Narcizo; Julia A. Rodrigues; Duarte Oom; José M. C. Pereira; Wilfrid Schroeder; Alberto W. Setzer (International Journal of Remote Sensing, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Coral reef resilience to thermal stress in the Eastern Tropical Pacific - Mauricio Romero‐Torres; Alberto Acosta; Ana M. Palacio‐Castro; Eric A. Treml; Fernando A. Zapata; David A. Paz‐García; James W. Porter (Global Change Biology, 2020)
Coral reefs worldwide are threatened by thermal stress caused by climate change. Especially devastating periods of coral loss frequently occur during El Niño‐Southern Oscillation (ENSO) events originating in the Eastern Tropical Pacific (ETP). El Niño‐induced thermal stress is considered the primary threat to ETP coral reefs. An increase in the frequency and intensity of ENSO events predicted in the coming decades threatens a pan‐tropical collapse of coral reefs. During the 1982–1983 El Niño, most reefs in the Galapagos Islands collapsed, and many more in the region were decimated by massive coral bleaching and mortality. However, after repeated thermal stress disturbances, such as those caused by the 1997–1998 El Niño, ETP corals reefs have demonstrated regional persistence and resiliency. Using a 44 year dataset (1970–2014) of live coral cover from the ETP, we assess whether ETP reefs exhibit the same decline as seen globally for other reefs. Also, we compare the ETP live coral cover rate of change with data from the maximum Degree Heating Weeks experienced by these reefs to assess the role of thermal stress on coral reef survival. We find that during the period 1970–2014, ETP coral cover exhibited temporary reductions following major ENSO events, but no overall decline. Further, we find that ETP reef recovery patterns allow coral to persist under these El Niño‐stressed conditions, often recovering from these events in 10–15 years. Accumulative heat stress explains 31% of the overall annual rate of change of living coral cover in the ETP. This suggests that ETP coral reefs have adapted to thermal extremes to date, and may have the ability to adapt to near‐term future climate‐change thermal anomalies. These findings for ETP reef resilience may provide general insights for the future of coral reef survival and recovery elsewhere under intensifying El Niño scenarios.

Near-complete genome sequence and biological properties of an allexivirus found in Senna rizzinii in Brazil - Taciana Miranda Alves; Quelmo Silva de Novaes; Alessandro de Paula; Viviana Marcela Camelo-García; Tatsuya Nagata; Joao Marcos Fagundes Silva; Jorge Alberto Marques Rezende; Elliot W. Kitajima (Archives of Virology, 2020)

Molecular and biological characterization of a putative new sobemovirus infecting Physalis peruviana - Arnaldo Esquivel Fariña; Eduardo Silva Gorayeb; Viviana Marcela Camelo-García; Jaíne Bonin; Tatsuya Nagata; Joao Marcos F. Silva; Amauri Bogo; Jorge Alberto Marques Rezende; Fabio Nascimento da Silva; Elliot W. Kitajima (Archives of Virology, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

Experimental dominant plant removal results in contrasting assembly for dominant and non‐dominant plants - Carlos Alberto Arnillas; Marc W. Cadotte (Ecology Letters, 2019)
Understanding why communities appear deterministically dominated by relatively few species is an age‐old debate in ecology. We hypothesised that the dominant and non‐dominant species in a community are governed by different assembly mechanisms where environmental conditions influence dominant species more than non‐dominant species. Further, dominant plants moderate the environment where non‐dominant species thrive, diminishing the influence of environmental filtering and increasing the influence of limiting similarity for non‐dominant species. We tested these hypotheses by removing two dominant species in five temperate meadows. We found that the composition of the non‐dominants diverged while the new dominants converged over time. Phylogenetic analyses suggested that habitat filtering and limiting similarity drove the new dominant species simultaneously. Conversely, non‐dominant community assembly appeared more unpredictable. These suggest that dominant species converged towards a predictable environmentally driven optimum, while non‐dominant species thrive in a moderated habitat, which probably reduced non‐dominant species predictability.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Spatial patterns of climate–growth relationships across species distribution as a forest management tool in Moncayo Natural Park (Spain) - Edurne Martínez del Castillo; Luis Alberto Longares; Roberto Serrano-Notivoli; Ute G. W. Sass-Klaassen; Martin de Luis (European Journal of Forest Research, 2019)

Real-World Variability in the Prediction of Intracranial Aneurysm Wall Shear Stress: The 2015 International Aneurysm CFD Challenge - Kristian Valen-Sendstad; Aslak W. Bergersen; Yuji Shimogonya; Leonid Goubergrits; Jan Bruening; Jordi Pallares; Salvatore Cito; Senol Piskin; Kerem Pekkan; Arjan J. Geers; Ignacio Larrabide; Saikiran Rapaka; et al. (Cardiovascular Engineering and Technology, 2018)

Climate change alterations to ecosystem dominance: how might sponge‐dominated reefs function? - James J. Bell; Alberto Rovellini; Simon K. Davy; Michael W. Taylor; Elizabeth A. Fulton; Matthew R. Dunn; Holly M. Bennett; Nora M. Kandler; Heidi M. Luter; Nicole S. Webster (Ecology, 2018)
Anthropogenic stressors are impacting ecological systems across the world. Of particular concern are the recent rapid changes occurring in coral reef systems. With ongoing degradation from both local and global stressors, future reefs are likely to function differently from current coral‐dominated ecosystems. Determining key attributes of future reef states is critical to reliably predict outcomes for ecosystem service provision. Here we explore the impacts of changing sponge dominance on coral reefs. Qualitative modelling of reef futures suggests that changing sponge dominance due to increased sponge abundance will have different outcomes for other trophic levels compared with increased sponge dominance as a result of declining coral abundance. By exploring uncertainty in the model outcomes we identify the need to (1) quantify changes in carbon flow through sponges, (2) determine the importance of food limitation for sponges, (3) assess the ubiquity of the recently described “sponge loop,” (4) determine the competitive relationships between sponges and other benthic taxa, particularly algae, and (5) understand how changing dominance of other organisms alters trophic pathways and energy flows through ecosystems. Addressing these knowledge gaps will facilitate development of more complex models that assess functional attributes of sponge‐dominated reef ecosystems.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Thermal buffering capacity of the germination phenotype across the environmental envelope of the Cactaceae - Charlotte E. Seal; Matthew I. Daws; Joel Flores; Pablo Ortega‐Baes; Guadalupe Galíndez; Pedro León‐Lobos; Ana Sandoval; Aldo Ceroni Stuva; Natali Ramírez Bullón; Patricia Dávila‐Aranda; Cesar A. Ordoñez‐Salanueva; Laura Yáñez‐Espinosa; et al. (Global Change Biology, 2017)
Recruitment from seeds is among the most vulnerable stage for plants as global temperatures change. While germination is the means by which the vast majority of the world's flora regenerate naturally, a framework for accurately predicting which species are at greatest risk of germination failure during environmental perturbation is lacking. Taking a physiological approach, we assess how one family, the Cactaceae, may respond to global temperature change based on the thermal buffering capacity of the germination phenotype. We selected 55 cactus species from the Americas, all geo‐referenced seed collections, reflecting the broad environmental envelope of the family across 70° of latitude and 3700 m of altitude. We then generated empirical data of the thermal germination response from which we estimated the minimum ( T b ), optimum ( T o ) and ceiling ( T c ) temperature for germination and the thermal time (θ 50 ) for each species based on the linearity of germination rate with temperature. Species with the highest T b and lowest T c germinated fastest, and the interspecific sensitivity of the germination rate to temperature, as assessed through θ 50 , varied tenfold. A left‐skewed asymmetry in the germination rate with temperature was relatively common but the unimodal pattern typical of crop species failed for nearly half of the species due to insensitivity to temperature change at T o . For 32 fully characterized species, seed thermal parameters correlated strongly with the mean temperature of the wettest quarter of the seed collection sites. By projecting the mean temperature of the wettest quarter under two climate change scenarios, we predict under the least conservative scenario (+3.7°C) that 25% of cactus species will have reduced germination performance, whilst the remainder will have an efficiency gain, by the end of the 21st century.

Influence of Testing Parameters on In Vitro Tramadol Release from Poloxamer Thermogels using the Immersion Cell Method - Lorina Bisharat; Diego R. Perinelli; Alberto Berardi; Giulia Bonacucina; Serena Logrippo; Feras W. Darwish Elhajji; Marco Cespi; Giovanni F. Palmieri (AAPS PharmSciTech, 2017)

Contrasting patterns of connectivity among endemic and widespread fire coral species (Millepora spp.) in the tropical Southwestern Atlantic - Júlia N. de Souza; Flávia L. D. Nunes; Carla Zilberberg; Juan A. Sanchez; Alvaro E. Migotto; Bert W. Hoeksema; Xaymara M. Serrano; Andrew C. Baker; Alberto Lindner (Coral Reefs, 2017)

Movement, connectivity and population structure of the intertidal fish Lipophrys pholis as revealed by otolith oxygen and carbon stable isotopes - Margarida Gama Carvalho; Claúdia Moreira; Joana F. M. F. Cardoso; Geert-Jan A. Brummer; Piet van Gaever; Henk W. van der Veer; Henrique Queiroga; Paulo Talhadas Santos; Alberto Teodorico Correia (Marine Biology Research, 2017)

Pseudomonas syringae Differentiates into Phenotypically Distinct Subpopulations During Colonization of a Plant Host - José S. Rufián; María‐Antonia Sánchez‐Romero; Diego López‐Márquez; Alberto P. Macho; John W. Mansfield; Dawn L. Arnold; Javier Ruiz‐Albert; Josep Casadesús; Carmen R. Beuzón (Environmental Microbiology, 2016)
Summary Bacterial microcolonies with heterogeneous sizes are formed during colonization of Phaseolus vulgaris by Pseudomonas syringae . Heterogeneous expression of structural and regulatory components of the P. syringae type III secretion system (T3SS), essential for colonization of the host apoplast and disease development, is likewise detected within the plant apoplast. T3SS expression is bistable in the homogeneous environment of nutrient‐limited T3SS‐inducing medium, suggesting that subpopulation formation is not a response to different environmental cues. T3SS bistability is reversible, indicating a non‐genetic origin, and the T3SS HIGH and T3SS LOW subpopulations show differences in virulence. T3SS bistability requires the transcriptional activator HrpL, the double negative regulatory loop established by HrpV and HrpG, and may be enhanced through a positive feedback loop involving HrpA, the main component of the T3SS pilus. To our knowledge, this is the first example of phenotypic heterogeneity in the expression of virulence determinants during colonization of a non‐mammalian host.

Drosophila suzukii population response to environment and management strategies - Nik G. Wiman; Daniel T. Dalton; Gianfranco Anfora; Antonio Biondi; Joanna C. Chiu; Kent M. Daane; Beverly Gerdeman; Angela Gottardello; Kelly A. Hamby; Rufus Isaacs; Alberto Grassi; Claudio Ioriatti; et al. (Journal of Pest Science, 2016)

A highly divergent isolate of tomato blistering mosaic virus from Solanum violaefolium - Rosana Blawid; Evelyn Anly Ishikawa Hayashi; Jorge Alberto Marques Rezende; Elliot W. Kitajima; Tatsuya Nagata (Virus Genes, 2016)

A DNA tool for the identification of heavily exploited Atlantic billfishes - Rodrigo R. Domingues; Gabriel Okuda; Andrea M. Bernard; Alberto F. Amorim; Juliana De Biasi; Alexandre W. S. Hilsdorf (Conservation Genetics Resources, 2015)

Connectivity structures local population dynamics: a long‐term empirical test in a large metapopulation system - Max C. N. Castorani; Daniel C. Reed; Filipe Alberto; Tom W. Bell; Rachel D. Simons; Kyle C. Cavanaugh; David A. Siegel; Peter T. Raimondi (Ecology, 2015)
Ecological theory predicts that demographic connectivity structures the dynamics of local populations within metapopulation systems, but empirical support has been constrained by major limitations in data and methodology. We tested this prediction for giant kelp Macrocystis pyrifera , a key habitat‐forming species in temperate coastal ecosystems worldwide, in southern California, USA. We combined a long‐term (22 years), large‐scale (~500 km coastline), high‐resolution census of abundance with novel patch delineation methods and an innovative connectivity measure incorporating oceanographic transport and source fecundity. Connectivity strongly predicted local dynamics (well‐connected patches had lower probabilities of extinction and higher probabilities of colonization, leading to greater likelihoods of occupancy) but this relationship was mediated by patch size. Moreover, the relationship between connectivity and local population dynamics varied over time, possibly due to temporal variation in oceanographic transport processes. Surprisingly, connectivity had a smaller influence on colonization relative to extinction, possibly because local ecological factors differ greatly between extinct and extant patches. Our results provide the first comprehensive evidence that southern California giant kelp populations function as a metapopulation system, challenging the view that populations of this important foundation species are governed exclusively by self‐replenishment.

Seascape drivers of M acrocystis pyrifera population genetic structure in the northeast P acific - Mattias L. Johansson; Filipe Alberto; Daniel C. Reed; Peter T. Raimondi; Nelson C. Coelho; Mary A. Young; Patrick T. Drake; Christopher A. Edwards; Kyle Cavanaugh; Jorge Assis; Lydia B. Ladah; Tom W. Bell; et al. (Molecular Ecology, 2015)
At small spatial and temporal scales, genetic differentiation is largely controlled by constraints on gene flow, while genetic diversity across a species' distribution is shaped on longer temporal and spatial scales. We assess the hypothesis that oceanographic transport and other seascape features explain different scales of genetic structure of giant kelp, M acrocystis pyrifera . We followed a hierarchical approach to perform a microsatellite‐based analysis of genetic differentiation in M acrocystis across its distribution in the northeast P acific. We used seascape genetic approaches to identify large‐scale biogeographic population clusters and investigate whether they could be explained by oceanographic transport and other environmental drivers. We then modelled population genetic differentiation within clusters as a function of oceanographic transport and other environmental factors. Five geographic clusters were identified: A laska/ C anada, central C alifornia, continental S anta B arbara, C alifornia C hannel I slands and mainland southern C alifornia/ B aja C alifornia peninsula. The strongest break occurred between central and southern C alifornia, with mainland S anta B arbara sites forming a transition zone between the two. Breaks between clusters corresponded approximately to previously identified biogeographic breaks, but were not solely explained by oceanographic transport. An isolation‐by‐environment ( IBE ) pattern was observed where the northern and southern C hannel I slands clustered together, but not with closer mainland sites, despite the greater distance between them. The strongest environmental association with this IBE pattern was observed with light extinction coefficient, which extends suitable habitat to deeper areas. Within clusters, we found support for previous results showing that oceanographic connectivity plays an important role in the population genetic structure of M acrocystis in the Northern hemisphere.

Mosaic maternal ancestry in the Great Lakes region of East Africa - Verónica Gomes; Maria Pala; Antonio Salas; Vanesa Álvarez-Iglesias; António Amorim; Alberto Gómez-Carballa; Ángel Carracedo; Douglas J. Clarke; Catherine Hill; Maru Mormina; Marie-Anne Shaw; David W. Dunne; et al. (Human Genetics, 2015)

Varied responses by yeast-like symbionts during virulence adaptation in a monophagous phloem-feeding insect - Jedeliza B. Ferrater; Alberto I. Naredo; Maria Liberty P. Almazan; Peter W. de Jong; Marcel Dicke; Finbarr G. Horgan (Arthropod-Plant Interactions, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Improved allometric models to estimate the aboveground biomass of tropical trees - Jérôme Chave; Maxime Réjou‐Méchain; Alberto Búrquez; Emmanuel Chidumayo; Matthew S. Colgan; Welington B.C. Delitti; Alvaro Duque; Tron Eid; Philip M. Fearnside; Rosa C. Goodman; Matieu Henry; Angelina Martínez‐Yrízar; et al. (Global Change Biology, 2014)
Terrestrial carbon stock mapping is important for the successful implementation of climate change mitigation policies. Its accuracy depends on the availability of reliable allometric models to infer oven‐dry aboveground biomass of trees from census data. The degree of uncertainty associated with previously published pantropical aboveground biomass allometries is large. We analyzed a global database of directly harvested trees at 58 sites, spanning a wide range of climatic conditions and vegetation types (4004 trees ≥ 5 cm trunk diameter). When trunk diameter, total tree height, and wood specific gravity were included in the aboveground biomass model as covariates, a single model was found to hold across tropical vegetation types, with no detectable effect of region or environmental factors. The mean percent bias and variance of this model was only slightly higher than that of locally fitted models. Wood specific gravity was an important predictor of aboveground biomass, especially when including a much broader range of vegetation types than previous studies. The generic tree diameter–height relationship depended linearly on a bioclimatic stress variable E , which compounds indices of temperature variability, precipitation variability, and drought intensity. For cases in which total tree height is unavailable for aboveground biomass estimation, a pantropical model incorporating wood density, trunk diameter, and the variable E outperformed previously published models without height. However, to minimize bias, the development of locally derived diameter–height relationships is advised whenever possible. Both new allometric models should contribute to improve the accuracy of biomass assessment protocols in tropical vegetation types, and to advancing our understanding of architectural and evolutionary constraints on woody plant development.

Joint Editorial—On the future of journal publications in hydrology - Günter Blöschl; András Bárdossy; Demetris Koutsoyiannis; Zbigniew W. Kundzewicz; Ian Littlewood; Alberto Montanari; Hubert Savenije (Hydrological Sciences Journal, 2014)

The landscape of fear: the missing link to understand top‐down and bottom‐up controls of prey abundance? - John W. Laundré; Lucina Hernández; Perla López Medina; Andrea Campanella; Jorge López-Portillo; Alberto González-Romero; Karina M. Grajales-Tam; Anna M. Burke; Peg Gronemeyer; Dawn M. Browning (Ecology, 2014)
Identifying factors that may be responsible for regulating the size of animal populations is a cornerstone in understanding population ecology. The main factors that are thought to influence population size are either resources (bottom‐up), or predation (top‐down), or interspecific competition (parallel). However, there are highly variable and often contradictory results regarding their relative strengths and influence. These varied results are often interpreted as indicating “shifting control” among the three main factors, or a complex, nonlinear relationship among environmental variables, resource availability, predation, and competition. We argue here that there is a “missing link” in our understanding of predator–prey dynamics. We explore whether the landscape‐of‐fear model can help us clarify the inconsistencies and increase our understanding of the roles, extent, and possible interactions of top‐down, bottom‐up, and parallel factors on prey population abundance. We propose two main predictions derived from the landscape‐of‐fear model: (1) for a single species, we suggest that as the makeup of the landscape of fear changes from relatively safe to relatively risky, bottom‐up impacts switch from strong to weak as top‐down impacts go from weak to strong; (2) for two or more species, interspecific competitive interactions produce various combinations of bottom‐up, top‐down, and parallel impacts depending on the dominant competing species and whether the landscapes of fear are shared or distinctive among competing species. We contend that these predictions could successfully explain many of the complex and contradictory results of current research. We test some of these predictions based on long‐term data for small mammals from the Chihuahuan Desert in the United States. and Mexico. We conclude that the landscape‐of‐fear model does provide reasonable explanations for many of the reported studies and should be tested further to better understand the effects of bottom‐up, top‐down, and parallel factors on population dynamics.

Can the red palm mite threaten the Amazon vegetation? - Manoel G. C. Gondim; Tatiane M. M. G. Castro; Alberto L. Marsaro; Denise Navia; José W. S. Melo; Peterson R. Demite; Gilberto J. de Moraes (Systematics and Biodiversity, 2012)

Erratum to: Contemporary Reviews of Mine Water Studies in Europe, Part 1 - Christian Wolkersdorfer; Rob Bowell; Jaime M. Amezaga; Adeline Kroll; Adam P. Jarvis; Ben Rees; Erik Puura; Wiel M. H. Miseré; Roy W. M. G. Wings; Peter Bajtoš; Leopold Weber; Blanka Sárváryné-Szentkatolnay; et al. (Mine Water and the Environment, 2012)

Mineralogical changes caused by grape production in a regosol from subtropical Brazilian climate - Edson Campanhola Bortoluzzi; Diovane Freire Moterle; Danilo dos Santos Rheinheimer; Carlos Alberto Casali; George W. Melo; Gustavo Brunetto (Journal of Soils and Sediments, 2012)

A multinational study of neurological performance in antiretroviral therapy-naïve HIV-1-infected persons in diverse resource-constrained settings - Kevin Robertson; Johnstone Kumwenda; Khuanchai Supparatpinyo; Jeanne H. Jiang; Scott Evans; Thomas B. Campbell; Richard W. Price; Robert Murphy; Colin Hall; Christina M. Marra; Cheryl Marcus; Baiba Berzins; et al. (Journal of NeuroVirology, 2011)

The integrated WRF/urban modelling system: development, evaluation, and applications to urban environmental problems - Fei Chen; Hiroyuki Kusaka; Robert Bornstein; Jason Ching; C. S. B. Grimmond; Susanne Grossman‐Clarke; Thomas Loridan; Kevin W. Manning; Alberto Martilli; Shiguang Miao; David Sailor; Francisco P. Salamanca; et al. (International Journal of Climatology, 2011)
To bridge the gaps between traditional mesoscale modelling and microscale modelling, the National Center for Atmospheric Research, in collaboration with other agencies and research groups, has developed an integrated urban modelling system coupled to the weather research and forecasting (WRF) model as a community tool to address urban environmental issues. The core of this WRF/urban modelling system consists of the following: (1) three methods with different degrees of freedom to parameterize urban surface processes, ranging from a simple bulk parameterization to a sophisticated multi‐layer urban canopy model with an indoor–outdoor exchange sub‐model that directly interacts with the atmospheric boundary layer, (2) coupling to fine‐scale computational fluid dynamic Reynolds‐averaged Navier–Stokes and Large‐Eddy simulation models for transport and dispersion (T&D) applications, (3) procedures to incorporate high‐resolution urban land use, building morphology, and anthropogenic heating data using the National Urban Database and Access Portal Tool (NUDAPT), and (4) an urbanized high‐resolution land data assimilation system. This paper provides an overview of this modelling system; addresses the daunting challenges of initializing the coupled WRF/urban model and of specifying the potentially vast number of parameters required to execute the WRF/urban model; explores the model sensitivity to these urban parameters; and evaluates the ability of WRF/urban to capture urban heat islands, complex boundary‐layer structures aloft, and urban plume T&D for several major metropolitan regions. Recent applications of this modelling system illustrate its promising utility, as a regional climate‐modelling tool, to investigate impacts of future urbanization on regional meteorological conditions and on air quality under future climate change scenarios. Copyright © 2010 Royal Meteorological Society

Nociceptin/Orphanin FQ Suppresses Adaptive Immune Responses In Vivo and at Picomolar Levels In Vitro - Benito Anton; Phillipe Leff; Joseph J. Meissler; Juan C. Calva; Rodolfo Acevedo; Alberto Salazar; Maura Matus; Anabel Flores; Martin Martinez; Martin W. Adler; John P. Gaughan; Toby K. Eisenstein (Journal of Neuroimmune Pharmacology, 2010)

Plants on Constant Alert: Elevated Levels of Jasmonic Acid and Jasmonate-Induced Transcripts in Caterpillar-Resistant Maize - Renuka Shivaji; Alberto Camas; Arunkanth Ankala; Jurgen Engelberth; James H. Tumlinson; W. Paul Williams; Jeff R. Wilkinson; Dawn Sywassink Luthe (Journal of Chemical Ecology, 2010)

Genetic control of the B cell response to LPS: opposing effects in peritoneal versus splenic B cell populations - A. M. Vale; E. Hayashi; A. Granato; H. W. Schroeder; M. Bellio; Alberto Nobrega (Immunogenetics, 2010)

The activity of amino acids produced by Paenibacillus macerans and from commercial sources against the root-knot nematode Meloidogyne exigua - Denilson F. Oliveira; Hudson W. P. Carvalho; Alessandro S. Nunes; Geraldo H. Silva; Vicente P. Campos; Helvécio M. S. Júnior; Alberto J. Cavalheiro (European Journal of Plant Pathology, 2009)

Expression of human papilloma virus type 16 antigens, specific targeting as well as formation of virus-like particles by HSV-1 amplicon vectors - Sabine Schenck; Elke Kehm; Alberto L. Epstein; Hanswalter Zentgraf; Martin Müller; Charles W. Knopf (Virus Genes, 2008)

Marine reserves: size and age do matter - Joachim Claudet; Craig W. Osenberg; Lisandro Benedetti‐Cecchi; Paolo Domenici; José‐Antonio García‐Charton; Ángel Pérez‐Ruzafa; Fabio Badalamenti; Just Bayle‐Sempere; Alberto Brito; Fabio Bulleri; Jean‐Michel Culioli; Mark Dimech; et al. (Ecology Letters, 2008)
Marine reserves are widely used throughout the world to prevent overfishing and conserve biodiversity, but uncertainties remain about their optimal design. The effects of marine reserves are heterogeneous. Despite theoretical findings, empirical studies have previously found no effect of size on the effectiveness of marine reserves in protecting commercial fish stocks. Using 58 datasets from 19 European marine reserves, we show that reserve size and age do matter: Increasing the size of the no‐take zone increases the density of commercial fishes within the reserve compared with outside; whereas the size of the buffer zone has the opposite effect. Moreover, positive effects of marine reserve on commercial fish species and species richness are linked to the time elapsed since the establishment of the protection scheme. The reserve size‐dependency of the response to protection has strong implications for the spatial management of coastal areas because marine reserves are used for spatial zoning.

A micro-scale investigation of melt production and extraction in the upper mantle based on silicate melt pockets in ultramafic xenoliths from the Bakony–Balaton Highland Volcanic Field (Western Hungary) - Enikő Bali; Alberto Zanetti; Csaba Szabó; David W. Peate; Tod E. Waight (Contributions to Mineralogy and Petrology, 2008)

Dispersal, recruitment and migratory behaviour in a hawksbill sea turtle aggregation - XIMENA VELEZ‐ZUAZO; WILLY D. RAMOS; ROBERT P. VAN DAM; CARLOS E. DIEZ; ALBERTO ABREU‐GROBOIS; W. OWEN MCMILLAN (Molecular Ecology, 2008)
We investigated the dispersal, recruitment and migratory behaviour of the hawksbill sea turtle ( Eretmochelys imbricata ), among different life‐history stages and demographic segments of the large hawksbill turtle aggregation at Mona Island, Puerto Rico. There were significant differences in both mitochondrial DNA (mtDNA) haplotype diversity and haplotype frequencies among the adult males, females and juveniles examined, but little evidence for temporal heterogeneity within these same groups sampled across years. Consistent with previous studies and the hypothesis of strong natal homing, there were striking mtDNA haplotype differences between nesting females on Mona Island and nesting females in other major Caribbean rookeries. Breeding males also showed strong, albeit weaker, genetic evidence of natal homing. Overall, Bayesian mixed‐stock analysis suggests that Mona Island was the natal rookery for 79% (65–94%) of males in the aggregation. In contrast, the Mona Island rookery accounted for only a small subset of the new juvenile recruits to the foraging grounds or in the population of older juvenile hawksbills turtles on Mona. Instead, both new recruits and the older juvenile hawksbill turtles on Mona more likely recruited from other Caribbean rookeries, suggesting that a mechanism besides natal homing must be influencing recruitment to feeding habitats. The difference in the apparent degree of natal homing behaviour among the different life‐history stages of hawksbill turtles at Mona Island underscores the complexity of the species’ life‐history dynamics and highlights the need for both local and regional conservation efforts.

Assessment of the processes controlling the seasonal variations of dissolved inorganic carbon in the North Sea - Yann Bozec; Helmuth Thomas; Laure-Sophie Schiettecatte; Alberto V. Borges; Khalid Elkalay; Hein J. W. de Baar (Limnology and Oceanography, 2006)
We used a seasonal North Sea data set comprising dissolved inorganic carbon (DIC), partial pressure of CO 2 ( p CO 2 ), and inorganic nutrients to assess the abiotic and biological processes governing the monthly variations of DIC. During winter, advection and air‐sea exchange of CO 2 control and increase the DIC content in the surface and deeper layers of the northern and central North Sea, with the atmosphere supplying CO 2 on the order of 0.2 mol C m −2 month −1 to these areas. From February to July, net community production (NCP) controls the seasonal variations of DIC in the surface waters of the entire North Sea, with a net uptake ranging from 0.5 to 1.4 mol C m −2 month −1 . During the August‐December period, NCP controls the seasonal variations of DIC in the southern North Sea, with a net release ranging from 0.5 to 0.8 mol C m −2 month −1 . Similarly, during the April‐August period in the deeper layer of the northern North Sea, the NCP was the main factor controlling DIC concentrations, with a net release ranging from 0.5 to 5.5 mol C m −2 month −1 . In the surface layer of the North Sea, NCP on the basis of DIC was 4.3 ± 0.4 mol C m −2 yr −1 , whereas, NCP on the basis of nitrate was 1.6 ± 0.2 mol C m −2 yr −1 . Under nutrient‐depleted conditions, preferential recycling (extracellular) of nutrients and intracellular mechanisms occurred and were responsible for the non‐Redfield uptake of DIC versus nitrate and phosphate.

Characterization of diazotrophic bacteria associated with maize: effect of plant genotype, ontogeny and nitrogen-supply - Luiz Fernando W. Roesch; Fabio L. Olivares; Luciane M. Pereira Passaglia; Pedro Alberto Selbach; Enilson L. Saccol de Sá; Flávio A. Oliveira de Camargo (World Journal of Microbiology and Biotechnology, 2006)

Cholinesterases in Aquatic Biomonitoring: Assay Optimization and Species-Specific Characterization for a California Native Fish - Andrew Whitehead; Susan L. Anderson; Alberto Ramirez; Barry W. Wilson (Ecotoxicology, 2005)

Mass spawning of reef corals within the Veracruz Reef System, Veracruz, Mexico - Carl R. Beaver; Sylvia A. Earle; Earle F. (Kip) Evans; Alberto Vazquez de la Cerda; John W. Tunnell (Coral Reefs, 2004)

Cloning, pharmacological characterisation and tissue distribution of a novel 5-HT 4 receptor splice variant, 5-HT 4(i) - Trond Brattelid; Ane M. Kvingedal; Kurt A. Krobert; Kjetil W. Andressen; Trond Bach; Marit E. Hystad; Alberto J. Kaumann; Finn Olav Levy (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

An Urban Surface Exchange Parameterisation for Mesoscale Models - Alberto Martilli; Alain Clappier; Mathias W. Rotach (Boundary-Layer Meteorology, 2002)

Paraoxonase promoter polymorphism T(–107)C and relative paraoxonase deficiency as determinants of risk of coronary artery disease - Ilia Leviev; Alberto Righetti; Richard W. James (Journal of Molecular Medicine, 2001)

The effect of age on the power/duration relationship and the intensity-domain limits in sedentary men - J. Alberto Neder; Paul W. Jones; Luiz E. Nery; Brian J. Whipp; J. Alberto Neder (European Journal of Applied Physiology, 2000)

Framework for scenario development in LCA - Hanna -Leena Pesonen; Tomas Ekvall; Günter Fleischer; Gjalt Huppes; Christina Jahn; Zbigniew S. Klos; Gerald Rebitzer; Guido W. Sonnemann; Alberto Tintinelli; Bo P. Weidema; Henrik Wenzel (The International Journal of Life Cycle Assessment, 2000)

Atlantic Basin Hurricanes: Indices of Climatic Changes - Christopher W. Landsea; Roger A. Pielke; Alberto M. Mestas-Nuñez; John A. Knaff (Climatic Change, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)